2000
DOI: 10.1093/jjco/hyd128
|View full text |Cite
|
Sign up to set email alerts
|

Useful Prognostic Panel Markers to Express the Biological Tumor Status in Resected Lung Adenocarcinomas

Abstract: The immunohistochemical expression of p53 and bcl-2 oncogenes and the expression of AgNOR cell proliferation index are critical values in the progression of lung adenocarcinomas. They can express the biological tumor status and indicate a more accurate prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
2
18
1
5
Order By: Relevance
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
“…In total, 42 studies published between 1991 and 2002 were selected for this systematic review (Tungekar et al, 1991;Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Costes et al, 1995;Giaccone et al, 1995;Harpole, Jr et al, 1995Bohm et al, 1996;Fontanini et al, 1996;Giatromanolaki et al, 1996a, b;Pujol et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Mehdi et al, 1998;Soomro et al, 1998;D'Amico et al, 1999D'Amico et al, , 2000Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Carvalho et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Pelosi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Carbognani et al, 2002;Minami et al, 2002;Rigau et al, 2002). Five were excluded because an identical patients cohort was used in another selected publication (references excluded/includ...…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total study sample size of 54 studies was 8522 with a mean of 158 (range, 45-535 patients). 23 cohorts (Pezzella et al, 1993;Fontanini et al, 1995;Fontanini et al, 1996;O'Neill et al, 1996;Apolinario et al, 1997;Koukourakis et al, 1997;Pastorino et al, 1997;Fontanini et al, 1998;Cox et al, 2000;Moldvay et al, 2000;Nguyen et al, 2000;Cox et al, 2001;Laudanski et al, 2001;Rigau et al, 2002;Swinson et al, 2002;Grossi et al, 2003;Swinson et al, 2004;Fokkema et al, 2006;Yaren et al, 2006;Ludovini et al, 2008;Anagnostou et al, 2010;Grimminger et al, 2010;Karpathiou et al, 2013) evaluated patients from Europe, 12 cohorts (Ritter et al, 1995;Anton et al, 1997;Kwiatkowski et al, 1998;D'Amico et al, 1999;Mehdi et al, 1999;Carvalho et al, 2000;Han et al, 2002;Huang et al, 2003;Poleri et al, 2003;Renouf et al, 2009;Anagnostou et al, 2010;Graziano et al, 2010) from America and 21 cohorts (Ohsaki et al, 1996;Higashiyama et al, 1997;…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…These factors could be used as prognostic markers of disease progression. Another study (11) demonstrated that early stages, as well as low expression of argyrophilic nucleolar organizer region (AgNOR), low p53 expression and high Bcl-2 expression, had a submitted to surgery due to bronchial carcinoid tumor and monitored for more 10 years in two university hospitals. (18) The authors used the following data to predict the individual risk for node metastases or distant metastases: age; gender; tumor-node-metastasis staging; tumor diameter; tumor location (central or peripheral); immunohistochemical index for p53, Ki67 and Bcl-2; and density of newly formed microvessels and fibers of the collagen-elastic system.…”
Section: P53mentioning
confidence: 99%